2008
DOI: 10.4049/jimmunol.181.4.2303
|View full text |Cite
|
Sign up to set email alerts
|

The RON Receptor Tyrosine Kinase Regulates IFN-γ Production and Responses in Innate Immunity

Abstract: Receptor tyrosine kinases are emerging as a class of key regulators of innate immune responses. We have shown previously that the RON receptor tyrosine kinases (murine Stk), expressed on tissue-resident macrophages, inhibit classical macrophage activation while promoting hallmarks of alternative activation, thus regulating the critical balance between the inflammatory and wound-healing properties of activated macrophages. We have also shown previously that RON−/− mice are more susceptible to in vivo endotoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 49 publications
(57 reference statements)
2
53
0
1
Order By: Relevance
“…It was found that pretreatment of macrophages with MSP before IFN-g and LPS resulted in complete inhibition of IL-12 production through suppression of p40 expression [43]. In support of this data, RON À/À mice exhibit increased IL12p40 level in response to LPS, accompanied with elevated IFN-g level [44]. Moreover, MSP inhibited the expression of IkBz -a nuclear IkB family member which is upregulated by LPS stimulation, a positive regulator for IL-12 p40 [38].…”
Section: Mechanisms Of Actionsupporting
confidence: 68%
“…It was found that pretreatment of macrophages with MSP before IFN-g and LPS resulted in complete inhibition of IL-12 production through suppression of p40 expression [43]. In support of this data, RON À/À mice exhibit increased IL12p40 level in response to LPS, accompanied with elevated IFN-g level [44]. Moreover, MSP inhibited the expression of IkBz -a nuclear IkB family member which is upregulated by LPS stimulation, a positive regulator for IL-12 p40 [38].…”
Section: Mechanisms Of Actionsupporting
confidence: 68%
“…MST1R encodes a cell surface receptor for macrophage-stimulating 1 (MST1, also known as MSP) with tyrosine kinase activity. Previous studies show that MST1R plays a critical function in host defense: (i) It is predominantly expressed in the tissue-resident macrophages, which promote tissue repair and inhibit inflammation by repressing the production of proinflammatory molecules induced by pathogens (14)(15)(16)(17) and (ii) MST1R expression is detected in the ciliated epithelial cells in the normal nasal mucosa, and activation of MST1R signaling can increase the ciliary motility to prevent chronic infection (18). Previous studies and our WES data strongly support the role of MST1R as an NPC susceptibility gene.…”
Section: Significancementioning
confidence: 99%
“…Whereas swine CAFO dust-induced TNF-␣ release in monocytes is impacted by endotoxins present in the dust (31), airway epithelial cells lack lipopolysaccharide signaling proteins such as CD14 and MD-2 (3,11) and are stimulated to release TNF-␣ by the peptidoglycan contained in CAFO dust (17). In vitro, we have found that small concentrations (200 pg/ml) of swine CAFO dust-stimulated TNF-␣ are capable of inducing the autocrine/paracrine stimulation of bronchial epithelial protein kinase C-ε (PKC-ε)-dependent IL-8 release (36).…”
mentioning
confidence: 99%